Kinerja Protokol Destination Sequence Distance Vector (DSDV) terhadap Serangan Wormhole pada MANET - Thelemanica Wicaksana; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
MANET is a wireless network that consists of many mobile devices that serve as nodes. Dedicated infrastructure or centralized access points are not owned by this free tool. MANET has several types of routing protocols, namely reactive, proactive, and hybrid protocols. DSDV is an example of a proactive routing protocol. However, MANET networks can also be attacked. One example of his attack is Wormhole. A wormhole is an attack that consists of 2 or more nodes in pairs and forms a tunnel to transmit data between wormhole nodes. This study tested two scenarios, namely using attacks and without wormhole attacks. The test was carried out using NS-2.35 with each scenario using random waypoint movements and varying the number of nodes and the number of pairs of wormhole nodes. The test is based on the test parameters using QoS. The QoS parameters used are throughput, end-to-end delay, and packet delivery ratio. The best throughput results are in the scenario of 60 nodes without wormhole attacks of 0.78 kbps. The best delay is in the 60 node scenario using one pair of wormhole attacks of 3.57926 seconds in the end-to-end results. At the same time, the best packet delivery ratio results are in the 80 node scenario without a wormhole attack of 35.8974%.